1973
DOI: 10.1080/00378941.1973.10839204
|View full text |Cite
|
Sign up to set email alerts
|

Fine structural studies of embryogenesis in a callus ofRanunculus sceleratus

Abstract: IDRésumé. -Les cultures de cals de /lanunculus sceleratus donnent naissance it un grand nombre d'embryoïdes qui gernwnt in situ ou lorsqu'ils sont st'•parés el transférés sur un milieu frais. Les pl'tites plantt•s t~n résultant, forment ulléricurcmt•nt des cmbryoïdes à partir de ecllult•s individuelles situées dans ]'{•pidermc de l'hypocotylc.Des études au microscope électronique ont montr.:, des similitudes entre les t•<•llult•s cmbryogènes des cals et celles des tiges de petites plantes pron•nant de l'(,pide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In both cases the cells of this region exhibited starch grains which were proposed to be somatic embryogenesis markers (Buffard-Morel et al 1992) while in normal roots they are known to act as statholiths (Mauseth 1995). The presence of starch grains in root primordia has also been reported in several other somatic embryogenesis systems (Thomas et al 1972, Street & Withers 1974, Ozias-Akins & Vasil 1982, Schwendiman et al 1988.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In both cases the cells of this region exhibited starch grains which were proposed to be somatic embryogenesis markers (Buffard-Morel et al 1992) while in normal roots they are known to act as statholiths (Mauseth 1995). The presence of starch grains in root primordia has also been reported in several other somatic embryogenesis systems (Thomas et al 1972, Street & Withers 1974, Ozias-Akins & Vasil 1982, Schwendiman et al 1988.…”
Section: Discussionmentioning
confidence: 92%
“…Such embryos were also described for Helianthus smithii Heiser (Laparra et al 1997), Cicer arietinum L. (Shri & Davis 1992), Sorghum (Thomas et al 1972. Laparra (1997) and Thomas (1972) interpreted them as an aborted somatic embryo, probably due to the low levels of auxin, insufficient for the establishment of the root pole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The route where the embryoids are formed directly from single cells and small cell groups in the medium corresponds to the origin of carrot embryoids described by Steward et al (1964) and Steward, Ammirato and Mapes (1970). The alternative route, where the embryoid remains attached to the aggregate and then is released at a late stage in development, is similar to the route described for embryoid production in Ranunculus sceleratus (Konar and Nataraja, 1965;Konar, Thomas and Street, 1972a;Thomas, Konar and Street, 1972), Atropa belladonna (Konar, Thomas and Street, 1972b), sorghum (Dunstan, Short and Thomas, 1978) and in other studies of carrot (Halperin and Wetherel, 1964;Halperin, 1967;Halperin and Jensen, 1967;McWilliam, Smith and Street, 1974). The celery embryoid appears to have the same varied path of development as the carrot.…”
Section: Discussionmentioning
confidence: 99%
“…The problem was whether the embryoid developed from a single isolated cell, in the same way as the zygote, or was derived from cells within the large cell mass of an aggregate. Most of the evidence suggested that the embryoids were initiated from surface cells of the cell aggregates and, where viable single cells were present, these first divided to form an aggregate from which embryoids were initiated from the surface as before (Halperin and Wetherel, 1964;Halperin, 1967;Halperin and Jensen, 1967;Thomas, Konar and Street, 1972;Konar, Thomas and Street, 1972;McWilliams, Smith and Street, 1974). At this early stage of its development the tissue culture embryoid is not strictly comparable to the plant embryo since the latter originates from a single isolated cell, the zygote which divides directly to form the embryo, whereas the embryoid arises from a relatively large mass of un differentia ted cells.…”
Section: Introductionmentioning
confidence: 99%